Impact of Pre-Hospital Antithrombotic Medication on the Outcome of Chronic and Acute Subdural Hematoma - Baraniskin, Alexander; Steffens, Carla; Harders, Albrecht; Schmiegel, Wolff; Schroers, Roland; Spangenberg, Peter (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Introduction Antithrombotic medication has proven efficacy in the treatment and prevention of cardiovascular and cerebrovascular diseases. A major disadvantage is the increased incidence of cerebral hemorrhages such as subdural hematomas (SDH). The impact of antithrombotic therapy on the outcome of subdural hematoma is not well characterized to date.Materials and Methods We retrospectively analyzed patients with subdural hematomas admitted to our hospital between 2005 and 2009. Antithrombotic medication, as well as other risk factors (age, sex, and preexisting diseases) were statistically analyzed in 476 consecutive patients for an independent association with inferior outcome, such as recurrent hematoma or in-hospital death. The patients had been evaluated and treated according to clinical standards for the management of severe head injury and were divided into groups with chronic SDH (cSDH) and acute SDH (aSDH), respectively.Results Of 312 patients with aSDH, 71 (22.8%) patients had at least one recurrence and 41 (13.1%) patients died in hospital. In the aSDH group, both the recurrence and the mortality were associated with anticoagulant therapy and with platelet aggregation inhibition. In the group of 163 patients with cSDH, 40 (24.5%) patients had a recurrence and 13 (7.9%) patients died within 9 weeks. Neither the application of platelet aggregation inhibitors nor the anticoagulant therapy were associated with recurrence or in-hospital mortality in this group.Conclusion Our results clearly indicate that prehospital antithrombotic therapy was independently associated with inferior outcome of patients with aSDH, while no association for patients with cSDH was observed.
Keywords: antithrombotic medication; subdural hematoma; outcome